Solar cell with MoS2 quantum dots as hole transport material
By using MoS2 quantum dots as hole transport material in solar cells, the problem of insufficient stability and efficiency of hole transport materials in the prior art is solved, and higher photoelectric conversion efficiency and long-term stability are achieved.
Patent Information
- Application Number
- CN202411472458.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-21
- Publication Date
- 2025-03-21
AI Technical Summary
The inorganic oxides used in existing solar cells as hole transport materials have problems such as poor stability, low brightness and poor transmission efficiency.
MoS2 quantum dots are used as hole transport material, and their photoelectric properties are optimized by adjusting the size and composition of the quantum dots, and the manufacturing cost is reduced through solution processing technology.
It improves the charge transport performance, light energy utilization and long-term stability of solar cells, reduces charge recombination, and enhances transportation characteristics.
Abstract
Description
Technical Field
[0001] The present application relates to the field of solar cell preparation, and in particular to a solar cell using MoS2 quantum dots as hole transport materials. Background Art
[0002] The design of photoactive materials plays a vital role in improving the collection capacity of batteries. The inorganic oxides currently used as hole extraction materials may have problems such as poor device stability, low brightness and poor transfer efficiency. However, two-dimensional transition metal sulfides (TMD, MX2) with excellent optical and electronic properties and two-dimensional van der Waals crystals with adjustable optical band gap and unique electrical properties have good prospects and have received widespread attention in electronic and optoelectronic devices. As the hole transport layer of solar cells, it is expected to obtain good charge transport performance. Therefore, it is necessary to explore two-dimensional transition metal sulfides (TMD, MX2) as hole transport materials for solar cells. Summary of the invention
[0003] The purpose of this application is to overcome the defects existing in the prior art. The solar cell provided by this application uses MoS2 quantum dots as hole transport materials. MoS2 quantum dots have high electron mobility, which helps to quickly and efficiently transport holes, thereby reducing charge recombination and improving the efficiency of the battery. The size of the quantum dots can be adjusted by the synthesis method, which allows the optoelectronic properties of the quantum dots to be optimized to suit a specific solar cell design. MoS2 quantum dots can absorb a wide range of spectra, which helps to improve the utilization of light energy by solar cells. MoS2 quantum dots have good chemical stability, which helps to improve the long-term stability and life of solar cells. MoS2 quantum dots can be prepared by solution processing technology, which helps to reduce manufacturing costs and allows solar cells to be manufactured on flexible substrates.
[0004] The first aspect of the present application provides a solar cell using MoS2 quantum dots as hole transport material, which includes, from bottom to top, a substrate, a transparent conductive film, a conductive polymer, a photosensitive material, and a metal electrode; the substrate is selected from glass; the transparent conductive film is selected from indium tin oxide (ITO); the conductive polymer is selected from poly(3,4-ethylenedioxythiophene):polystyrene sulfonate (PEDOT:PSS); and the photosensitive material includes MoS2 quantum dots.
[0005] In some embodiments, the metal electrode is selected from Al.
[0006] The second aspect of the present application discloses a method for preparing a solar cell using MoS2 quantum dots as a hole transport material, which is used to prepare the above-mentioned solar cell, comprising the steps of:
[0007] S1, coating ITO on glass, cleaning and drying the substrate; S2, spin-casting PEDOT:PSS on ITO, baking at 150-200°C for 20-30 minutes to form a PSS / ITO substrate; S3, spin-coating MoS2 quantum dots on the PSS / ITO substrate and baking at 15°C for 30 minutes; S4, dissolving p-type material and n-type material in a mixed solvent of chlorobenzene / 1,8-diiodooctane to form a mixture; S5, spin-coating the mixture in S4 at a speed of 900-1000rpm for 1-2 minutes and coating it on the substrate deposited on the MoS2 quantum dots; S6, finally, thermally evaporating the Al electrode under vacuum.
[0008] In some embodiments, in S1, the cleaning solvent is deionized water, acetone and isopropanol.
[0009] In some embodiments, the spin casting conditions in S2 are: 3000-5000 rpm spin casting for 1-2 min.
[0010] In some embodiments, the conditions for the operation from S3 to S4 are: under a N2 environment, the substrate in S3 is moved into a glove box, and then the operation in S4 is performed.
[0011] In some embodiments, in S3, the conditions for spin coating MoS2 quantum dots on the PSS / ITO substrate are: spin coating MoS2 quantum dots at 4000 rpm for 1 min, and / or in S6, the vacuum is set to 10 -6 Torr.
[0012] In some embodiments, the p-type material is selected from any one of silicon carbide doped with aluminum (Al) or boron (B), and gallium nitride doped with magnesium (Mg), and / or the n-type material is selected from any one of indium phosphide doped with arsenic (As), antimony (Sb) or phosphorus (P), silicon carbide doped with nitrogen (N) or phosphorus (P), and gallium nitride doped with silicon (Si).
[0013] In some embodiments, the preparation method of MoS2 quantum dots includes: mixing MoS2 powder and potassium sodium tartrate under N2 atmosphere to form a mixture; transferring the mixture into a homemade reactor, maintaining it at 200-250°C for 24 hours and then depositing it into a selected solvent to obtain dispersed MoS2 quantum dots dispersed in distilled water, and thoroughly dialyzing the aqueous solution in deionized water with a dialysis membrane; centrifuging the dialyzed aqueous solution, and freeze-drying the quantum dot solution to obtain MoS2 quantum dots.
[0014] In some embodiments, the dialyzed aqueous solution compound is centrifuged at 10,000-12,000 rpm in a centrifuge tube for 10-15 min.
[0015] Beneficial effects:
[0016] MoS2 quantum dots have higher hole mobility and smoother bands when used as hole extraction materials, thus significantly enhancing the transport properties. The band gap can be easily tuned by adjusting the size and composition of the quantum dots, which makes MoS2 quantum dots suitable as electron / hole materials in solar cells. DETAILED DESCRIPTION
[0017] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by technicians in the technical field to which this application belongs; the terms used herein are only for the purpose of describing specific embodiments and are not intended to limit this application; the terms "including" and "having" in the description and claims of this application and any variations thereof are intended to cover non-exclusive inclusions.
[0018] Reference to "embodiments" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present application. The appearance of the phrase in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments.
[0019] To solve the problems raised in the background technology, the first aspect of the present application provides a solar cell with MoS2 quantum dots as hole transport material, which includes, from bottom to top, a substrate, a transparent conductive film, a conductive polymer, a photosensitive material, and a metal electrode; the substrate is selected from glass; the transparent conductive film is selected from indium tin oxide (ITO); the conductive polymer is selected from poly(3,4-ethylenedioxythiophene):polystyrene sulfonate (PEDOT:PSS); and the photosensitive material includes MoS2 quantum dots.
[0020] Two-dimensional transition metal sulfides (TMDs, MX2) with excellent optical and electronic properties and two-dimensional van der Waals crystals with tunable optical band gaps and unique electrical properties have good prospects and have received extensive attention in electronic and optoelectronic devices, being used as electron / hole transport materials to replace inorganic oxides, thereby significantly improving the power conversion efficiency of solar cells. This enhancement is achieved because they have obvious advantages, such as suitable work function values and widely tunable band gaps, and they are also easy to process.
[0021] MoS2 quantum dots have high electron mobility and the size of the quantum dots can be tuned through synthetic methods, which allows the optoelectronic properties of the quantum dots to be optimized to suit specific solar cell designs.
[0022] MoS2 quantum dots can absorb a wide range of light spectra, which helps to improve the utilization of light energy in solar cells. MoS2 quantum dots have good chemical stability, which helps to improve the long-term stability and lifetime of solar cells. Quantum dots have a high specific surface area, which increases the contact area with the photosensitive layer and helps to improve the hole extraction efficiency. By changing the size and shape of quantum dots, their band structure can be adjusted to better align with the energy levels of the photosensitive layer. MoS2 quantum dots do not contain heavy metals or toxic elements and are environmentally friendly. MoS2 quantum dots can be compatible with many types of photosensitive materials, providing flexibility in designing new solar cells. The synthesis and processing technology of MoS2 quantum dots has good scalability and is suitable for large-scale production. The surface of MoS2 quantum dots can be functionalized to reduce charge recombination at the interface. MoS2 quantum dots show a synergistic effect in achieving high performance because they generate additional photocurrent and favorable hole extraction, as well as their modification of the PEDOT:PSS surface.
[0023] In some embodiments, the metal electrode is selected from Al. Al is an excellent conductive material that helps to effectively collect and transmit the current generated by the solar cell. Al has a high reflectivity and can reflect unabsorbed light back to the photosensitive layer of the cell, thereby increasing the absorption and utilization of light. Aluminum has a high melting point, which helps to maintain performance in the high temperature operating environment of the solar cell.
[0024] The second aspect of the present application discloses a method for preparing a solar cell using MoS2 quantum dots as a hole transport material, which is used to prepare the above-mentioned solar cell, comprising the steps of:
[0025] S1, coating ITO on glass, cleaning and drying the substrate; S2, spin-casting PEDOT:PSS on ITO, baking at 150-200°C for 20-30 minutes to form a PSS / ITO substrate; S3, spin-coating MoS2 quantum dots on the PSS / ITO substrate and baking at 15°C for 30 minutes; S4, dissolving p-type material and n-type material in a mixed solvent of chlorobenzene / 1,8-diiodooctane to form a mixture; S5, spin-coating the mixture in S4 at a speed of 900-1000rpm for 1-2 minutes and coating it on the substrate deposited on the MoS2 quantum dots; S6, finally, thermally evaporating the Al electrode under vacuum.
[0026] MoS2 quantum dots can be used to modify the PEDOT:PSS layer, improve the interface between PEDOT:PSS and the active layer, reduce charge recombination and improve hole extraction efficiency. PEDOT:PSS is a known conductive polymer, while MoS2 quantum dots have high electron mobility, and their combination can provide a more efficient charge transfer channel. MoS2 quantum dots can increase the absorption of light, especially at specific wavelengths, which helps to improve the photoelectric conversion efficiency of solar cells.
[0027] MoS2 quantum dots help improve the chemical stability of the PEDOT:PSS layer, especially under harsh environmental conditions. By using MoS2 quantum dots, the amount of PEDOT:PSS used can be reduced, thereby reducing material costs. MoS2 quantum dots can increase the light transmittance of the PEDOT:PSS layer, allowing more light to reach the active layer. MoS2 quantum dots can form a heterostructure with PEDOT:PSS, which helps separate photogenerated charge pairs and reduce recombination.
[0028] The PEDOT:PSS layer combined with MoS2 quantum dots provides better mechanical flexibility, which is beneficial for making flexible solar cells. The addition of MoS2 quantum dots improves the thermal stability of the PEDOT:PSS layer, which helps maintain performance under high-temperature operating conditions. MoS2 quantum dots can help adjust energy levels, thereby increasing the open-circuit voltage of solar cells. MoS2 quantum dots help reduce interfacial defects in the PEDOT:PSS layer, which are often the centers of charge recombination. Both MoS2 quantum dots and PEDOT:PSS are environmentally friendly materials, and their combination helps to make more environmentally friendly solar cells.
[0029] In some embodiments, in S1, the solvents used for the cleaning are deionized water, acetone and isopropanol. Deionized water is pure water after the ionic impurities in the water are removed, and has a very high purity. Acetone is a colorless transparent liquid that is easily soluble in water and a variety of organic solvents. It is a polar solvent with good solubility and can dissolve a variety of organic substances. It is also a commonly used cleaning agent and detergent. Acetone is highly volatile and can evaporate quickly without leaving any traces. Isopropanol is used in the cleaning process of solar cells due to its rapid volatilization, good solubility, non-conductivity, bactericidal effect, material compatibility, environmental protection, economic benefits and safety.
[0030] In some embodiments, the conditions of the spin casting described in S2 are: 3000-5000rpm spin casting for 1-2min. The centrifugal force generated by high-speed rotation helps the liquid to spread evenly on the substrate, reducing uneven thickness and defects. By adjusting the rotation speed and time, the thickness of the film can be precisely controlled. High-speed rotation helps the rapid evaporation of the solvent and reduces the residual solvent in the film. The contact time between the liquid and the substrate is longer during the rotation process, which helps to improve the adhesion between the film and the substrate. The shear force generated during the rotation process helps to remove bubbles and particles in the liquid, thereby obtaining a smoother film surface. The rapid evaporation of the solvent during the spin casting process reduces pollution to the environment.
[0031] In some embodiments, the conditions for the operation from S3 to S4 are: under a N2 environment, the substrate in S3 is moved into a glove box, and then the operation in S4 is performed.
[0032] In some embodiments, in S3, the conditions for spin coating MoS2 quantum dots on the PSS / ITO substrate are: spin coating MoS2 quantum dots at 4000 rpm for 1 min, and / or in S6, the vacuum is set to 10 -6 Torr.
[0033] In some embodiments, the p-type material is selected from any one of silicon carbide doped with aluminum (Al) or boron (B), and gallium nitride doped with magnesium (Mg), and / or the n-type material is selected from any one of indium phosphide doped with arsenic (As), antimony (Sb) or phosphorus (P), silicon carbide doped with nitrogen (N) or phosphorus (P), and gallium nitride doped with silicon (Si).
[0034] In some embodiments, the method for preparing the MoS2 quantum dots comprises:
[0035] MoS2 powder and potassium sodium tartrate are mixed under a N2 atmosphere to form a mixture; the mixture is transferred into a homemade reactor, maintained at 200-250°C for 24 hours, and then deposited into a selected solvent to obtain dispersed MoS2 quantum dots dispersed in distilled water, and the aqueous solution is thoroughly dialyzed in deionized water with a dialysis membrane; the compound of the dialyzed aqueous solution is centrifuged, and the quantum dot solution is freeze-dried to obtain MoS2 quantum dots.
[0036] In some embodiments, MoS2 powder and sodium potassium tartrate are mixed by grinding under N2 atmosphere, the mass ratio of the two being 1:10, and the mixture is formed by grinding. MoS2 powder and sodium potassium tartrate can be fully mixed by grinding, which helps to improve the electrical conductivity of the material. The grinding process can reduce the particle size of MoS2 and increase its specific surface area, which is beneficial for catalytic reactions and other applications. Grinding can introduce defects in the sheet structure of MoS2, which can serve as active sites to enhance the catalytic performance of the material. The presence of sodium potassium tartrate may help prevent the agglomeration of MoS2 nanosheets during the grinding process and maintain their dispersibility. Sodium potassium tartrate may help to improve the chemical stability of MoS2, especially the edge active sites that may be generated during the grinding process. Sodium potassium tartrate may form a complex with the surface of MoS2 to change its surface properties.
[0037] In some embodiments, the dialyzed aqueous solution compound is centrifuged at 10,000-12,000 rpm in a centrifuge tube for 10-15 min.
[0038] In summary, MoS2 quantum dots can significantly enhance the transport properties because of their higher hole mobility and smoother surface when used as hole extraction materials. The band gap can be easily adjusted by adjusting the size and composition of the quantum dots, which makes it suitable as an electron / hole material in solar cells. When used in the hole extraction layer of organic photovoltaic cells, MoS2 quantum dots can show a higher synergistic effect, which is beneficial to the extraction of holes.
[0039] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.
Claims
1. A solar cell using MoS2 quantum dots as hole transport material, characterized in that: From bottom to top, it includes a substrate, a transparent conductive film, a conductive polymer, a photosensitive material, and a metal electrode; The substrate is selected from glass; The transparent conductive film is selected from indium tin oxide (ITO); The conductive polymer is selected from poly(3,4-ethylenedioxythiophene):polystyrene sulfonate (PEDOT:PSS); The photosensitive material includes MoS2 quantum dots.
2. The solar cell using MoS2 quantum dots as hole transport material according to claim 1, characterized in that: The metal electrode is selected from Al.
3. A method for preparing a solar cell using MoS2 quantum dots as a hole transport material, for preparing the solar cell according to any one of claims 1-2, characterized in that: Includes steps: S1, coating ITO on glass, cleaning and drying the substrate; S2, spin casting PEDOT:PSS on ITO and baking at 150-200°C for 20-30 minutes to form a PSS / ITO substrate; S3, spin-coating MoS2 quantum dots on PSS / ITO substrate and baking at 15 °C for 30 min; S4, dissolving the p-type material and the n-type material in a mixed solvent of chlorobenzene / 1,8-diiodooctane to form a mixture; S5, spin coating the mixture in S4 at a speed of 900-1000 rpm for 1-2 minutes, coating the substrate deposited on the MoS2 quantum dots; S6, finally, thermally evaporate the Al electrode under vacuum.
4. The method for preparing a solar cell using MoS2 quantum dots as a hole transport material according to claim 3, characterized in that: In S1, the cleaning solvents are deionized water, acetone and isopropanol.
5. The method for preparing a solar cell using MoS2 quantum dots as a hole transport material according to claim 3, characterized in that: The conditions of the spin casting in S2 are: 3000-5000 rpm spin casting for 1-2 min.
6. The method for preparing a solar cell using MoS2 quantum dots as a hole transport material according to claim 3, characterized in that: The conditions for the operation from S3 to S4 are: under N2 environment, the substrate in S3 is moved into a glove box, and then the operation in S4 is performed.
7. The method for preparing a solar cell using MoS2 quantum dots as a hole transport material according to claim 3, characterized in that: In S3, the conditions for spin coating MoS2 quantum dots on the PSS / ITO substrate are: spin coating MoS2 quantum dots at 4000 rpm for 1 min, and / or in S6, the vacuum is set to 10 -6 Torr.
8. The method for preparing a solar cell using MoS2 quantum dots as a hole transport material according to claim 3, characterized in that: The p-type material is selected from any one of silicon carbide doped with aluminum (Al) and boron (B), and gallium nitride doped with magnesium (Mg), and / or the n-type material is selected from any one of indium phosphide doped with arsenic (As), antimony (Sb) or phosphorus (P), silicon carbide doped with nitrogen (N) and phosphorus (P), and gallium nitride doped with silicon (Si).
9. The method for preparing a solar cell using MoS2 quantum dots as a hole transport material according to claim 3, characterized in that: The preparation method of the MoS2 quantum dots comprises: Mixing MoS2 powder and potassium sodium tartrate under N2 atmosphere to form a mixture; The above mixture was transferred into a homemade reactor and maintained at 200-250°C for 24 h before being deposited into a selected solvent to obtain dispersed MoS2 quantum dots dispersed in distilled water, and the aqueous solution was dialyzed thoroughly in deionized water using a dialysis membrane; The dialyzed aqueous solution was centrifuged, and the quantum dot solution was freeze-dried to obtain MoS2 quantum dots.
10. The method for preparing a solar cell using MoS2 quantum dots as a hole transport material according to claim 9, characterized in that: The conditions for centrifuging the dialyzed aqueous solution are: centrifuging in a centrifuge tube at 10000-12000 rpm for 10-15 min.